On track to becoming a cosmopolitan invasive species: First record of the box tree moth Cydalima perspectalis (Lepidoptera: Crambidae) in the African continent - Haddad, Karim; Kalaentzis, Konstantinos; Demetriou, Jakovos (ENTOMOLOGIA HELLENICA, 2020)
Native to E. Asia, the box tree moth Cydalima perspectalis (Walker, 1859) has managed to establish itself, and gradually expand its distribution, across Europe, Asia and recently America. This publication documents the first known record of the invasive species in Africa. The moth was observed in Constantine, Algeria in 2018 and was later identified as C. perspectalis. Possible scenarios of its introduction on the continent, as well as potential ecological implications, are discussed.